Using Internet Resources in Remote Learning of English as a Foreign Language - Ibrahim, Mona Kamal; Spitsyna, Natalya A.; Isaeva, Anastasia Y. (Opción, 1970)
Remote learning plays an important role in modern education, including language education. Thus, the objectives of the research are: to conduct a survey among university students on the topic of remote learning of the English language; based on the results, to draw conclusions, identify possible problems and develop recommendations that can help eliminate the disadvantages of the remote learning of the English language. A total of 650 fourth-year students from Russian universities participated in the survey. There were nine questions in the survey. According to the results of the study, students have a positive attitude towards remote learning courses in English. However, they believe that this practice has not been sufficiently developed in their educational institutions. Several solutions were proposed to address this problem: promotion of remote learning of foreign languages; explaining the importance of informal methods of remote language learning; creation of online language forums under the auspices of educational institutions.